Chopinowskie narracje z „dziecięcego pokoju”. Mistrz w czasopismach i publikacjach dla najmłodszych w XIX wieku – rekonesans - Zajkowska, Joanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
The article discusses the biographical accounts and stories about Frédéric Chopin published in the most representative children’s magazines of the turn of the twentieth century: Wieczory Rodzinne (Family evenings), Przyjaciel Dzieci (Children’s friend) and Moje Pisemko (My little magazine). A kind of complementary role to them is played by the analysis of Janina Sedlaczkówna’s 1891 book Dwaj mistrze: opowiadanie o życiu Artura Grottgera i Fryderyka Chopina (Two maestros: a story about the lives of Artur Grottger and Frédéric Chopin) and Teresa Jadwiga Papi’s stories from 1898 of the same title Dwaj mistrze (Two maestros) about Chopin and Moniuszko. The collected comments and conclusions are presented in relation to twentieth- century biographical texts about Chopin.